All-silicon Beta molecular sieve catalyst for ozone elimination and preparation and application methods thereof
By impregnating Ag and Mn elements on the all-silicon Beta molecular sieve in two steps to form AgMnO2 active substances, the problem of poor hydrophobicity of the existing catalyst support is solved, and the efficient and moisture-resistant ozone elimination effect is achieved, which significantly improves the performance and service life of the catalyst. .
Patent Information
- Application Number
- CN202411513669.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-10-28
- Publication Date
- 2025-01-14
- Estimated Expiration
- 2044-10-28
AI Technical Summary
The carriers of existing ozone elimination catalysts such as Mn2O3 and activated carbon have poor hydrophobic properties, resulting in a short service life and cannot meet the water resistance requirements. The research focuses on the installation of precious metals such as Pt and Pd, and ignores the relatively hydrophobic molecular sieve catalysts and cheapness. metal Ag, Mn.
Using all-silicon Beta molecular sieve as a support, the Ag and Mn elements are supported by two-step impregnation method to form a catalyst with a three-dimensional twelve-membered ring BEA structure, and the synergistic action of Ag and Mn is used to generate AgMnO2 active substances, which improves catalytic performance and enhances moisture resistance. .
It achieves ozone elimination effects with high catalytic activity, moisture resistance and long service life, and performs excellently in low temperature and high airspeed conditions, surpassing the performance of traditional catalysts.
Smart Images

Figure CN119303614A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to a catalyst preparation technology, and in particular to an all-silicon Beta molecular sieve catalyst for ozone elimination and a preparation and application method thereof. Background Art
[0002] Ozone is often used for wastewater treatment, air purification, drinking water bleaching, and sterilization of medical equipment, but the use of ozone will introduce new problems. For example, excessively high concentrations of ozone can damage the user's eyes, respiratory tract, etc., and in severe cases can cause chronic pulmonary obstruction. In addition, electronics factories, printers, lasers, ultraviolet equipment, and automobile exhaust (secondary pollution of photochemical smog) all produce a large amount of ozone, especially in large cities where ozone will form and accumulate, causing great environmental damage. At present, ozone has replaced PM2.5 as the main air pollutant, so the situation of ozone pollution control is severe.
[0003] The ozone removal methods currently used in the industry mainly include thermal decomposition, catalytic decomposition, activated carbon adsorption, liquid medicine absorption, etc. Compared with other removal methods, the catalytic decomposition method has the advantages of low energy consumption, good safety, rapid reaction, high treatment efficiency, and less secondary pollution, and is widely used in research.
[0004] The core of the catalytic decomposition method lies in the catalyst, but in the existing technologies related to ozone removal catalysts, most of them use Mn2O3 (such as CN109603817A, CN112473665A, CN110711579A) and activated carbon (such as CN201110031051.7) as carriers. Most of these mainstream catalysts have poor hydrophobic properties, resulting in a short service life. Even the most excellent Mn2O3 carrier still cannot meet the actual requirements in terms of water resistance.
[0005] Therefore, developing an ozone decomposition catalyst with high catalytic performance and good water resistance is particularly important for solving the problem of ozone pollution control. Summary of the invention
[0006] The technical problem to be solved by the present invention is to overcome the defects existing in the prior art and provide an all-silicon Beta molecular sieve catalyst for ozone elimination and a preparation and application method thereof.
[0007] In order to solve the above technical problems, the solution adopted by the present invention is:
[0008] Provided is an all-silicon Beta molecular sieve catalyst for ozone elimination. The catalyst is obtained by using an all-silicon Beta molecular sieve with a three-dimensional twelve-membered ring BEA structure as a carrier and loading Ag and Mn elements in a precursor solution on the molecular sieve in sequence through a two-step impregnation method; wherein the mass percentage of the Ag element in the catalyst is 1.0-10.0%, and the mass percentage of the Mn element in the catalyst is 1.0-10.0%.
[0009] The present invention further provides a method for preparing the all-silicon Beta molecular sieve catalyst, which is to load the Ag and Mn elements in the precursor solution on the BEA structure molecular sieve in sequence by a two-step impregnation method; specifically comprising:
[0010] (1) adding powdered all-silicon Beta molecular sieve to a precursor solution containing an Ag element, mixing them evenly and performing an impregnation treatment; subjecting the impregnated mixture to ultrasonication, stirring and rotary evaporation to obtain a solid, and then subjecting it to drying and calcining to obtain a powdered catalyst precursor;
[0011] (2) adding the catalyst precursor to the precursor solution containing the Mn element, mixing them evenly and performing an impregnation treatment; the impregnated mixture is subjected to ultrasonication, stirring and rotary evaporation to obtain a solid, and then subjected to drying and calcination to obtain a powdered all-silicon Beta molecular sieve catalyst;
[0012] By changing the dosage relationship between the two precursor solutions and the all-silicon Beta molecular sieve, the mass proportion of Ag and Mn elements in the all-silicon Beta molecular sieve catalyst is adjusted.
[0013] As a preferred embodiment of the present invention, the all-silicon Beta molecular sieve has a three-dimensional twelve-membered ring BEA structure, and its surface has mesopores with a specific surface area of 500 to 700 m 2 .g -1 .
[0014] As a preferred embodiment of the present invention, the precursor solution containing the Ag element refers to a silver nitrate solution, and the precursor solution containing the Mn element refers to a manganese nitrate solution. The concentrations of the two precursor solutions are both 0.1 mol / L.
[0015] As a preferred embodiment of the present invention, the immersion treatment is carried out at room temperature for 10 to 12 hours.
[0016] As a preferred embodiment of the present invention, the ultrasonic treatment is carried out at room temperature for 1 hour at a frequency of 45 Hz.
[0017] As a preferred embodiment of the present invention, the temperature during the rotary evaporation treatment is 80° C. and the rotation speed is 70 rpm.
[0018] As a preferred embodiment of the present invention, the temperature during the drying process is 80° C. and the time is 2 hours.
[0019] As a preferred embodiment of the present invention, the heating rate during the calcination process is 5°C / min, the calcination temperature is 450-550°C, and the calcination time is 4-6h; after the calcination is completed, the calcined product is naturally cooled to room temperature.
[0020] The present invention also provides a method for catalytically eliminating ozone using the above-mentioned all-silicon Beta molecular sieve catalyst, comprising: loading the catalyst in a fixed bed reaction device, and then passing the reaction gas containing ozone and saturated water vapor through the catalyst bed in a continuous flow manner, and decomposing the ozone into oxygen through a catalytic reaction; in the catalytic reaction process, the reaction temperature is controlled to be 30°C, and the volume hourly space velocity of the reaction gas is 840000h -1 The relative humidity during the reaction is 65-85%, and the reaction time is 6-120h.
[0021] Description of the invention principle:
[0022] 1. In the prior art, it is a common practice to use molecular sieves to carry precious metal active components to prepare various catalysts. However, it is rare to see the use of molecular sieves as carriers in the preparation of catalysts for ozone elimination; most of them use Mn2O3 or activated carbon as carriers. The reason is that molecular sieves as carriers usually have surface defects, which affect the mass transfer during the ozone catalytic reaction and lead to a decrease in catalytic activity. The use of Mn2O3 or activated carbon can avoid the above problems. Therefore, researchers generally have inertial thinking and have long compared the effects of various precious metals based on Mn2O3 or activated carbon carriers. The research direction is also limited to adjusting the details such as the type of precious metals, reaction mode, and the proportion of active components.
[0023] Therefore, based on the prevailing technical prejudice, during the research on ozone depletion catalysts, relevant technicians will only consider molecular sieves with larger specific surface areas such as MCM-41, as well as relatively expensive metals such as Pt and Pd, even if there are public records of using molecular sieves to load metals; they will not consider more hydrophobic molecular sieve catalysts and relatively cheap metals such as Ag and Mn.
[0024] 2. Different from the prior art, the present invention innovatively proposes: using all-silicon Beta molecular sieve and silver and manganese precursors, through a series of treatments such as mixing, impregnation, ultrasound, stirring, rotary evaporation, drying, and calcination, the Ag and Mn elements in the precursor solution are successively loaded on the molecular sieve through a two-step impregnation method to obtain an all-silicon Beta molecular sieve catalyst.
[0025] In this process, the ozone decomposition activity does not decrease due to the defects on the surface of the all-silicon Beta molecular sieve. On the contrary, the defects on its surface anchor the metal Ag and Mn on the surface of the all-silicon molecular sieve better. This means that what is usually regarded as a disadvantage in the application of molecular sieves has become a technical advantage in the present invention.
[0026] 3. The present invention impregnates metal Ag and Mn into the all-silicon Beta molecular sieve in two steps, and the dispersion of the metal is better, and the effect is better than the operation of impregnating Ag and Mn at the same time. At the beginning of the impregnation process, metal Ag exists in the form of nanoclusters, and its valence state is mostly 0; while Mn appears in the form of MnO2 or Mn2O3 (mostly MnO2). Therefore, when the catalyst is used for ozone catalytic reaction, at the beginning, the surface of MnO2 is unstable after contacting with ozone and is very easy to reconstruct. At this time, Ag enters the MnO2 interface to generate AgMnO2 and become a new active substance. This discovery is brand new and has never been publicly reported in relevant literature in the field of ozone decomposition technology.
[0027] Theoretical calculations show that the ozone catalytic decomposition activity of AgMnO2 is better than other commonly used Ag-based catalysts, which is one of the reasons why the catalyst of the present invention can catalyze ozone elimination at low temperature. At the same time, since the hydrophobicity of the surface of the all-silicon Beta molecular sieve is better than that of other molecular sieves, Mn2O3, activated carbon, etc., the catalyst has better moisture resistance at high space velocity, and thus has a longer service life.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] 1. The present invention proposes to use a two-step impregnation method to load the Ag and Mn elements in the precursor solution on the molecular sieve in sequence, which is a new process in the preparation technology of multi-component active center catalysts.
[0030] 2. The catalytic performance of the catalyst of the present invention is better than that of most catalysts reported so far, and performs well in terms of moisture resistance, high space velocity, and low temperature catalysis.
[0031] 3. The present invention is the first to use the all-silicon Beta molecular sieve with BEA topology structure as a carrier for ozone removal catalyst, providing a new idea for catalyst research. BRIEF DESCRIPTION OF THE DRAWINGS
[0032] Figure 1 It is a schematic diagram of the catalytic reaction process in the present invention.
[0033] Figure 2 The XRD patterns of the catalyst samples obtained in Examples 1 to 6 and the all-silicon Beta sample are shown below.
[0034] Figure 3These are the XRD patterns corresponding to the catalyst samples obtained in Examples 3, 7, 9 and 10.
[0035] Figure 4 The catalytic activity test results (ozone elimination curves) of the catalyst samples obtained in Examples 1 to 6 are shown.
[0036] Figure 5 The catalytic activity test results (ozone elimination curves) of the catalyst samples obtained in Examples 3, 7, 9 and 10 are shown.
[0037] Figure 6 The catalytic activity test results (ozone elimination curves) of the catalyst samples in Example 3 and Comparative Examples 1-6 are shown.
[0038] Figure 7 These are the test results of the moisture-resistant ozone removal activity of the catalyst sample in Example 17.
[0039] Figure 8 It is the long-period ozone elimination curve of the catalyst samples in Example 3 and Comparative Example 7.
[0040] Fig. 9 This is the SEM image of the catalyst sample in Example 3.
[0041] Fig.10 This is the SEM image of the catalyst sample in Comparative Example 3.
[0042] Fig.11 This is the HRTEM image of the catalyst sample in Example 3.
[0043] Fig.12 These are the nitrogen adsorption diagrams of the catalyst samples in Examples 1, 3, 6 and Comparative Examples 1, 2, 7.
[0044] Fig.13 This is the contact angle diagram of the catalyst sample in Example 3.
[0045] Fig.14 This is the contact angle diagram of the catalyst sample in Comparative Example 7.
[0046] Fig.15 This is the HRTEM of AgMnO2 that appears after the catalyst reacts for 1 hour in Example 3. Specific implementation plan
[0047] The preferred embodiments of the present invention are further described in detail below. It should be understood by those skilled in the art that the embodiments are only to help understand the present invention and should not be regarded as specific limitations of the present invention.
[0048] Part I: Implementation scheme, evaluation system and embodiments of the present invention
[0049] 1. Implementation of the present invention
[0050] The present invention proposes that the Ag and Mn elements in the precursor solution are loaded on the molecular sieve of BEA structure in sequence by a two-step impregnation method; specifically comprising:
[0051] (1) The powder specific surface area is 500-700m 2 .g -1 The all-silicon Beta molecular sieve is added to the precursor solution containing the Ag element, mixed evenly and impregnated; the impregnated mixture is subjected to ultrasonication, stirring and rotary evaporation to obtain a solid, and then dried and calcined to obtain a powdered catalyst precursor;
[0052] The all-silicon Beta molecular sieve has a three-dimensional twelve-membered ring BEA structure, with mesopores on its surface and a specific surface area of 500 to 700 m 2 .g -1 The precursor solution containing the Ag element is a silver nitrate solution with a concentration of 0.1 mol / L.
[0053] The impregnation treatment is carried out at room temperature for 10 to 12 hours; the ultrasonic treatment is carried out at room temperature for 1 hour at a frequency of 45 Hz; the temperature during the rotary evaporation treatment is 80°C and the rotation speed is 70 rpm; the temperature during the drying treatment is 80°C and the time is 2 hours; the heating rate during the roasting treatment is 5°C / min, the roasting temperature is 450 to 550°C, and the roasting time is 4 to 6 hours; after the roasting is completed, it is naturally cooled to room temperature.
[0054] (2) adding the catalyst precursor to the precursor solution containing the Mn element, mixing them evenly and performing an impregnation treatment; the impregnated mixture is subjected to ultrasonication, stirring and rotary evaporation to obtain a solid, and then subjected to drying and calcination to obtain a powdered all-silicon Beta molecular sieve catalyst;
[0055] The precursor solution containing the Mn element refers to a manganese nitrate solution with a concentration of 0.1 mol / L.
[0056] The operating conditions of the impregnation treatment, ultrasound, stirring, rotary evaporation, drying and roasting in this step are all consistent with those in the previous step.
[0057] (3) By changing the dosage relationship between the two precursor solutions and the all-silicon Beta molecular sieve, the mass percentage of Ag and Mn elements in the all-silicon Beta molecular sieve catalyst can be adjusted, so that in the final all-silicon Beta molecular sieve catalyst, the mass percentage of Ag element in the catalyst is 1.0-10.0%, and the mass percentage of Mn element in the catalyst is 1.0-10.0%.
[0058] The all-silicon Beta molecular sieve catalyst can be used to catalytically eliminate ozone, and the specific method of use includes:
[0059] The catalyst is loaded in a fixed bed reaction device, and then the reaction gas containing ozone and saturated water vapor is passed through the catalyst bed in a continuous flow manner, and the ozone is decomposed into oxygen through a catalytic reaction; during the catalytic reaction process, the reaction temperature is controlled to be 30°C, and the volume hourly space velocity of the reaction gas is 840,000 h -1 The relative humidity during the reaction is 65-85%, and the reaction time is 6-120h.
[0060] 2. To verify the performance of the catalyst, the present invention builds a catalyst evaluation system in the following manner:
[0061] like Figure 1 As shown in the figure, the evaluation system mainly consists of three parts: gas path and control system, catalytic reaction device system and online analysis and detection system. The gases used in the experiment (except water) are all provided by the air generating pump. After the air comes out of the air generating pump, it passes through the mass flow meter and enters the mixing tube and enters the bubbler and ozone generator respectively. Water is brought into the mixed gas by air as a balance gas through the bubbling method, and ozone is generated after the air enters the ozone generator. In the catalytic reaction system, a reaction tube made of quartz glass is used, with an inner diameter of 4mm and an outer diameter of 6mm. The catalytic reaction device system has two reaction tubes, one of which is a bypass reaction tube and the other is a reaction tube with a catalyst. The two reaction tubes are switched by a three-way switch. In the middle of the reaction tube is a catalyst with a mesh size of 40 to 60 meshes, and both ends are quartz wool to support the catalyst and make it evenly distributed; there is only quartz wool in the bypass reaction tube, but no catalyst, which is used for control experiments to test the reaction space velocity and ozone concentration. The reaction tube is placed in a resistance furnace, and the center of the catalyst and the thermocouple are ensured to be in the temperature control zone of the resistance furnace. The program temperature control of the resistance furnace is controlled by a temperature controller. The online analysis and detection is to quantitatively detect the ozone concentration by the gas after the catalytic reaction entering the American ozone detector Model 202 2B.
[0062] When conducting catalytic activity tests, the reaction atmosphere conditions and the ratio of each raw gas in the mixed gas can be controlled within the following ranges: water relative humidity is 0-85%, ozone concentration is 0-40ppm, and volume hourly space velocity is 600000-840000h -1 .
[0063] The preparation and verification process of the all-silicon Beta molecular sieve catalyst of the present invention is described in detail below through a number of examples.
[0064] 3. Specific content of Examples 1-16
[0065] Example 1
[0066] (1) Preparation of catalyst
[0067] Weigh 2 grams of a substance with a specific surface area of 500 to 700 m 2 .g -1 The all-silicon Beta molecular sieve powder was weighed with 11.30g of silver nitrate solution with a molar concentration of 0.1mol / L. The molecular sieve powder was added to the silver nitrate solution, first immersed at room temperature for 10h, then ultrasonically treated at a frequency of 45Hz for 1h, and then stirred for 1h; the solid was obtained by rotary evaporation at 80℃ and a speed of 70rpm, and then dried at 80℃ for 2h. The solid was heated to 450℃ at a rate of 5℃ / min, kept warm and calcined for 4h, and then naturally cooled to room temperature to obtain the all-silicon Beta molecular sieve catalyst precursor.
[0068] Weigh 1 g of all-silicon Beta molecular sieve catalyst precursor and 1.85 g of manganese nitrate solution with a molar concentration of 0.1 mol / L, and follow the same operating method as the above process to obtain the final 6% Ag-1% Mn / all-silicon Beta molecular sieve catalyst through impregnation, ultrasound, stirring, rotary evaporation, drying, and calcination.
[0069] The X-ray diffraction curve of the all-silicon Beta molecular sieve catalyst obtained in this example is as follows: Figure 2 As shown in Figure 1, the positions of the diffraction peaks are all standard characteristic peaks of BEA topological molecular sieves, indicating that the metal is well dispersed on the catalyst. Fig.12 As shown, there is a hysteresis loop in its nitrogen adsorption diagram, indicating that the catalyst has mesopores.
[0070] (2) Catalyst performance verification
[0071] In order to verify the high catalytic activity of 6% Ag-1% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0072] The all-silicon Beta molecular sieve catalyst was prepared in this example. Under the test conditions, the ozone elimination rate was above 95% in 6 hours and above 93% in 12 hours. The ozone elimination curve of the catalyst varied with time. Figure 4 shown.
[0073] Example 2
[0074] (1) Preparation of catalyst
[0075] Referring to the preparation method in Example 1, 3.70 g of a manganese nitrate solution with a molar concentration of 0.1 mol / L was weighed, and the rest was exactly the same as in Example 1 to prepare a 6% Ag-2% Mn / all-silicon Beta molecular sieve catalyst.
[0076] The X-ray diffraction curve of the all-silicon Beta molecular sieve catalyst obtained in this example is as follows: Figure 2 As shown, the positions of the diffraction peaks are all standard characteristic peaks of BEA topological structure molecular sieves, indicating that the metal is well dispersed on the catalyst.
[0077] (2) Catalyst performance verification
[0078] In order to verify the high catalytic activity of 6% Ag-2% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0079] The all-silicon Beta molecular sieve catalyst was prepared in this example. Under the test conditions, the ozone elimination rate was above 99% in 6 hours and above 98% in 12 hours. The ozone elimination curve of the catalyst varied with time as shown in FIG. Figure 4 shown.
[0080] Example 3
[0081] (1) Preparation of catalyst
[0082] Referring to the preparation method in Example 1, 7.40 g of a manganese nitrate solution with a molar concentration of 0.1 mol / L was weighed, and the rest was exactly the same as in Example 1 to prepare a 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst.
[0083] The X-ray diffraction curve of the all-silicon Beta molecular sieve catalyst obtained in this example is as follows: Figure 2 , 3 As shown in Figure 1, the positions of the diffraction peaks are all standard characteristic peaks of BEA topological molecular sieves, indicating that the metal is well dispersed on the catalyst. Fig.12 As shown in the figure, there is a hysteresis loop in its nitrogen adsorption diagram, indicating that the catalyst has mesopores. Fig. 9 No metal is seen in the Beta, indicating that the metal is well dispersed on the Beta. Fig.13 As shown, it has a certain degree of hydrophobicity. Its HRTEM image is as follows Fig.11 As shown in the figure, it means that part of the silver element on the catalyst is in the Ag0 state at the beginning. After 1 hour of reaction, a more active substance AgMnO2 will appear on the catalyst surface. Its HRTEM is as follows Fig.15 shown.
[0084] (2) Catalyst performance verification
[0085] In order to verify the high catalytic activity of 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1, the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0086] In this embodiment, an all-silicon Beta molecular sieve catalyst is prepared. Under the above test conditions, the ozone elimination rate is more than 99% in 6 hours, more than 99% in 12 hours, and more than 85% in 120 hours. The ozone elimination curve changes with time as shown in FIG. Figure 4-8 As shown. When other conditions remain unchanged, the reaction time space velocity is changed to 600000h -1 ,720000h -1 It was found that under the test conditions of changing the reaction space velocity, the ozone elimination rate was above 99% in 6 hours and above 99% in 12 hours, which reflects the high catalytic activity of the all-silicon Beta molecular sieve catalyst.
[0087] Example 4
[0088] (1) Preparation of catalyst
[0089] Referring to the preparation method in Example 1, 11.10 g of a manganese nitrate solution with a molar concentration of 0.1 mol / L was weighed, and the rest was exactly the same as in Example 1 to prepare a 6% Ag-6% Mn / all-silicon Beta molecular sieve catalyst.
[0090] The X-ray diffraction curve of the all-silicon Beta molecular sieve catalyst obtained in this example is as follows: Figure 2 As shown, the positions of the diffraction peaks are all standard characteristic peaks of BEA topological structure molecular sieves, indicating that the metal is well dispersed on the catalyst.
[0091] (2) Catalyst performance verification
[0092] In order to verify the high catalytic activity of 6% Ag-6% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0093] The all-silicon Beta molecular sieve catalyst was prepared in this example. Under the test conditions, the ozone elimination rate was above 99% in 6 hours and above 98% in 12 hours. The ozone elimination curve of the catalyst varied with time as shown in FIG. Figure 4 shown.
[0094] Example 5
[0095] (1) Preparation of catalyst
[0096] Referring to the preparation method in Example 1, 14.80 g of a manganese nitrate solution with a molar concentration of 0.1 mol / L was weighed, and the rest was exactly the same as in Example 1 to prepare a 6% Ag-8% Mn / all-silicon Beta molecular sieve catalyst.
[0097] The X-ray diffraction curve of the all-silicon Beta molecular sieve catalyst obtained in this example is as follows: Figure 2 As shown, the positions of the diffraction peaks are all standard characteristic peaks of BEA topological structure molecular sieves, indicating that the metal is well dispersed on the catalyst.
[0098] (2) Catalyst performance verification
[0099] In order to verify the high catalytic activity of the all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0100] In this example, a 6% Ag-8% Mn / all-silicon Beta molecular sieve catalyst was prepared. Under the test conditions, the ozone elimination rate in 6 hours was above 98%, and the ozone elimination rate in 12 hours was above 97%. The ozone elimination curve changes with time as shown in FIG. Figure 4 shown.
[0101] Example 6
[0102] (1) Preparation of catalyst
[0103] Referring to the preparation method in Example 1, 18.50 g of a manganese nitrate solution with a molar concentration of 0.1 mol / L was weighed, and the rest was exactly the same as in Example 1 to prepare a 6% Ag-10% Mn / all-silicon Beta molecular sieve catalyst.
[0104] The X-ray diffraction curve of the all-silicon Beta molecular sieve catalyst obtained in this example is as follows: Figure 2 As shown in Figure 1, the positions of the diffraction peaks are all standard characteristic peaks of BEA topological molecular sieves, indicating that the metal is well dispersed on the catalyst. Fig.12 As shown, there is a hysteresis loop in its nitrogen adsorption diagram, indicating that the catalyst has mesopores.
[0105] (2) Catalyst performance verification
[0106] In order to verify the high catalytic activity of 6% Ag-10% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0107] The all-silicon Beta molecular sieve catalyst was prepared in this example. Under the test conditions, the ozone elimination rate was above 98% in 6 hours and above 96% in 12 hours. The ozone elimination curve of the catalyst varied with time as shown in FIG. Figure 4 shown.
[0108] Example 7
[0109] (1) Preparation of catalyst
[0110] Referring to the preparation method in Example 3, 18.83 g of a silver nitrate solution with a molar concentration of 0.1 mol / L and 14.80 g of a manganese nitrate solution with a molar concentration of 0.1 mol / L were weighed, and the rest was exactly the same as in Example 3 to prepare a 10% Ag-8% Mn / all-silicon Beta molecular sieve catalyst.
[0111] The X-ray diffraction curve of the all-silicon Beta molecular sieve catalyst obtained in this example is as follows: Figure 3 As shown, the positions of the diffraction peaks are all standard characteristic peaks of BEA topological structure molecular sieves, indicating that the metal is well dispersed on the catalyst.
[0112] (2) Catalyst performance verification
[0113] In order to verify the high catalytic activity of the 10% Ag-8% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0114] In this example, an all-silicon Beta molecular sieve catalyst was prepared. Under the test conditions, the ozone elimination rate was above 99% in 6 hours and above 99% in 12 hours. The ozone elimination curve changes with time as shown in Figure 5 shown.
[0115] Example 8
[0116] (1) Preparation of catalyst
[0117] Referring to the preparation method in Example 1, 1.88 g of a silver nitrate solution with a molar concentration of 0.1 mol / L and 1.85 g of a manganese nitrate solution with a molar concentration of 0.1 mol / L were weighed, and the rest was exactly the same as in Example 1 to prepare a 1% Ag-1% Mn / all-silicon Beta molecular sieve catalyst.
[0118] (2) Catalyst performance verification
[0119] In order to verify the catalytic activity of 1% Ag-1% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1, the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0120] The all-silicon Beta molecular sieve catalyst prepared in this embodiment has an ozone elimination rate of more than 15% in 12 hours under the test conditions.
[0121] Example 9
[0122] (1) Preparation of catalyst
[0123] Referring to the preparation method in Example 1, 3.77 g of a silver nitrate solution with a molar concentration of 0.1 mol / L and 3.70 g of a manganese nitrate solution with a molar concentration of 0.1 mol / L were weighed, and the rest was exactly the same as in Example 1 to prepare a 2% Ag-2% Mn / all-silicon Beta molecular sieve catalyst.
[0124] The X-ray diffraction curve of the all-silicon Beta molecular sieve catalyst obtained in this example is as follows: Figure 3 As shown, the positions of the diffraction peaks are all standard characteristic peaks of BEA topological structure molecular sieves, indicating that the metal is well dispersed on the catalyst.
[0125] (2) Catalyst performance verification
[0126] In order to verify the catalytic activity of 2% Ag-2% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0127] In this example, an all-silicon Beta molecular sieve catalyst was prepared. Under the test conditions, the ozone elimination rate was more than 90% in 6 hours and more than 85% in 12 hours. The ozone elimination curve changes with time as shown in the figure. Figure 5 shown.
[0128] Example 10
[0129] (1) Preparation of catalyst
[0130] Referring to the preparation method in Example 1, 7.53 g of a silver nitrate solution with a molar concentration of 0.1 mol / L and 7.40 g of a manganese nitrate solution with a molar concentration of 0.1 mol / L were weighed, and the rest was exactly the same as in Example 1 to prepare a 4% Ag-4% Mn / all-silicon Beta molecular sieve catalyst.
[0131] The X-ray diffraction curve of the all-silicon Beta molecular sieve catalyst obtained in this example is as follows: Figure 3 As shown, the positions of the diffraction peaks are all standard characteristic peaks of BEA topological structure molecular sieves, indicating that the metal is well dispersed on the catalyst.
[0132] (2) Catalyst performance verification
[0133] In order to verify the high catalytic activity of 4% Ag-4% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0134] The all-silicon Beta molecular sieve catalyst was prepared in this example. Under the test conditions, the ozone elimination rate was above 98% in 6 hours and above 97% in 12 hours. The ozone elimination curve changes with time as shown in the figure. Figure 5 shown.
[0135] Embodiment 11
[0136] (1) Preparation of catalyst
[0137] Referring to the preparation method in Example 3, except changing the calcination temperature to 500° C., the other steps are exactly the same as in Example 3 to prepare a 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst.
[0138] (2) Catalyst performance verification
[0139] In order to verify the high catalytic activity of 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0140] In this embodiment, an all-silicon Beta molecular sieve catalyst is prepared. When the calcination temperature is 500° C., under the test conditions, the ozone elimination rate is above 99% in 6 hours and above 99% in 12 hours.
[0141] Example 12
[0142] (1) Preparation of catalyst
[0143] Referring to the preparation method in Example 3, except changing the calcination temperature to 550° C., the other steps are exactly the same as in Example 3 to prepare a 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst.
[0144] (2) Catalyst performance verification
[0145] In order to verify the high catalytic activity of 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0146] In this embodiment, an all-silicon Beta molecular sieve catalyst is prepared. When the calcination temperature is 550° C., under the test conditions, the ozone elimination rate is above 99% in 6 hours and above 99% in 12 hours.
[0147] Embodiment 13
[0148] (1) Preparation of catalyst
[0149] Referring to the preparation method in Example 3, except changing the calcination time to 5 hours, the other steps are exactly the same as in Example 3 to prepare a 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst.
[0150] (2) Catalyst performance verification
[0151] In order to verify the high catalytic activity of 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0152] In this embodiment, an all-silicon Beta molecular sieve catalyst is prepared. When the calcination time is 5 hours, under the test conditions, the ozone elimination rate is more than 99% in 6 hours and more than 99% in 12 hours.
[0153] Embodiment 14
[0154] (1) Preparation of catalyst
[0155] Referring to the preparation method in Example 3, except changing the calcination time to 6 hours, the other steps are exactly the same as Example 3 to prepare a 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst.
[0156] (2) Catalyst performance verification
[0157] In order to verify the high catalytic activity of 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0158] In this embodiment, an all-silicon Beta molecular sieve catalyst is prepared. When the calcination time is 6 hours, under the test conditions, the ozone elimination rate is more than 99% in 6 hours and more than 99% in 12 hours.
[0159] Embodiment 15
[0160] (1) Preparation of catalyst
[0161] Referring to the preparation method in Example 1, except that the impregnation time was changed to 11 h, the other steps were exactly the same as in Example 1 to prepare a 6% Ag-1% Mn / all-silicon Beta molecular sieve catalyst.
[0162] (2) Catalyst performance verification
[0163] In order to verify the high catalytic activity of 6% Ag-1% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0164] In this embodiment, an all-silicon Beta molecular sieve catalyst is prepared. When the calcination time is 6 hours, under the test conditions, the ozone elimination rate in 6 hours is more than 95%, and the ozone elimination rate in 12 hours is more than 93%.
[0165] Example 16
[0166] (1) Preparation of catalyst
[0167] Referring to the preparation method in Example 1, except that the impregnation time was changed to 12 h, the other steps were exactly the same as in Example 1 to prepare a 6% Ag-1% Mn / all-silicon Beta molecular sieve catalyst.
[0168] (2) Catalyst performance verification
[0169] In order to verify the high catalytic activity of 6% Ag-1% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0170] In this embodiment, an all-silicon Beta molecular sieve catalyst is prepared. When the calcination time is 6 hours, under the test conditions, the ozone elimination rate in 6 hours is more than 95%, and the ozone elimination rate in 12 hours is more than 93%.
[0171] Embodiment 17
[0172] (1) Preparation of catalyst
[0173] Referring to the preparation method in Example 3, a 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst was prepared.
[0174] (2) Catalyst performance verification
[0175] In order to verify the high catalytic activity of the 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65%, 70%, 80%, 85% and a space velocity of 840000 h -1, the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0176] When other conditions remain unchanged, it has been verified that under RH=85%, the ozone elimination efficiency can still reach more than 96% after 12 hours, which reflects the high catalytic activity of the all-silicon Beta molecular sieve catalyst. The ozone elimination curve changes with time and humidity as shown in Figure 7 shown.
[0177] Embodiment 18
[0178] (1) Preparation of catalyst
[0179] Referring to the preparation method in Example 3, a 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst was prepared.
[0180] (2) Catalyst performance verification
[0181] In order to verify the high catalytic activity of the 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 The ozone elimination test was carried out under the conditions of ozone concentration of 10ppm, 20ppm, 30ppm and reaction temperature of 30℃.
[0182] With other conditions unchanged, it was found that under the test conditions of changing the ozone concentration, the ozone elimination rate was above 99% in 6 hours and above 99% in 12 hours, reflecting the high catalytic activity of the all-silicon Beta molecular sieve catalyst.
[0183] Embodiment 19
[0184] (1) Preparation of catalyst
[0185] Referring to the preparation method in Example 3, a 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst was prepared.
[0186] (2) Catalyst performance verification
[0187] In order to verify the high catalytic activity of the 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 600000 h -1 ,720000h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0188] With other conditions unchanged, it was found that under the test conditions of changing the reaction space velocity, the ozone elimination rate in 6 hours was above 99%, and the ozone elimination rate in 12 hours was above 99%, reflecting the high catalytic activity of the all-silicon Beta molecular sieve catalyst.
[0189] Part II Catalyst preparation and performance analysis of comparative examples
[0190] Comparative Example 1
[0191] (1) Preparation of catalyst
[0192] The all-silicon Beta molecular sieve was replaced with an all-silicon ZSM-5 molecular sieve, and the rest was the same as in Example 3.
[0193] A 6% Ag-4% Mn / all-silicon ZSM-5 molecular sieve catalyst was prepared.
[0194] The nitrogen adsorption results of the all-silicon ZSM-5 molecular sieve catalyst obtained in this comparative example are as follows Fig.12 As shown, there is no hysteresis loop in its nitrogen adsorption diagram, indicating that there are no mesopores in the catalyst.
[0195] (2) Catalyst performance verification
[0196] In order to verify the catalytic activity of 6% Ag-4% Mn / all-silicon ZSM-5 molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0197] The all-silicon ZSM-5 molecular sieve catalyst was prepared in this comparative example. Under the test conditions, the ozone elimination rate was more than 97% in 6 hours and more than 92% in 12 hours. The ozone elimination curve changes with time as shown in the figure. Figure 6 shown.
[0198] Comparative Example 2
[0199] (1) Preparation of catalyst
[0200] The all-silicon Beta molecular sieve was replaced with Al2O3, and the rest was the same as in Example 3 to prepare a 6% Ag-4% Mn / Al2O3 catalyst.
[0201] The nitrogen adsorption results of the Al2O3 catalyst obtained in this comparative example are as follows Fig.12 As shown, there is no hysteresis loop in its nitrogen adsorption diagram, indicating that there are no mesopores in the catalyst.
[0202] (2) Catalyst performance verification
[0203] In order to verify the catalytic activity of 6% Ag-4% Mn / Al2O3 catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0204] The Al2O3 catalyst prepared in this comparative example has an ozone elimination rate of more than 90% in 6 hours and more than 85% in 12 hours under the test conditions. The ozone elimination curve changes with time as shown in the figure. Figure 6 shown.
[0205] Comparative Example 3
[0206] (1) Preparation of catalyst
[0207] The all-silicon Beta molecular sieve was replaced with α-Mn2O3, and no manganese nitrate solution was added. The other conditions were the same as in Example 3, and a 6% Ag / α-Mn2O3 catalyst was prepared.
[0208] Its SEM image is Fig.10 No metal is seen in the sample, indicating that the metal is well dispersed on α-Mn2O3.
[0209] (2) Catalyst performance verification
[0210] In order to verify the catalytic activity of 6% Ag / α-Mn2O3 catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0211] The α-Mn2O3 catalyst prepared in this comparative example has an ozone elimination rate of more than 79% in 6 hours and more than 73% in 12 hours under the test conditions. The ozone elimination curve changes with time as shown in the figure. Figure 6 shown.
[0212] Comparative Example 4
[0213] (1) Preparation of catalyst
[0214] The all-silicon Beta molecular sieve was replaced with MCM-41 molecular sieve, and the other procedures were the same as in Example 3 to prepare a 6% Ag-4% Mn / MCM-41 catalyst.
[0215] (2) Catalyst performance verification
[0216] In order to verify the catalytic activity of 6% Ag-4% Mn / MCM-41 molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0217] The MCM-41 molecular sieve catalyst prepared in this comparative example has an ozone elimination rate of more than 77% in 6 hours and more than 71% in 12 hours under the test conditions. The ozone elimination curve changes with time as shown in FIG. Figure 6 shown.
[0218] Comparative Example 5
[0219] (1) Preparation of catalyst
[0220] The all-silicon Beta molecular sieve was replaced with TiO2 molecular sieve, and the other procedures were the same as in Example 3 to prepare a 6% Ag-4% Mn / TiO2 catalyst.
[0221] (2) Catalyst performance verification
[0222] In order to verify the catalytic activity of 6% Ag-4% Mn / TiO2 molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0223] The TiO2 catalyst prepared in this comparative example has an ozone elimination rate of more than 76% in 6 hours and more than 63% in 12 hours under the test conditions. The ozone elimination curve changes with time as shown in the figure. Figure 6 shown.
[0224] Comparative Example 6
[0225] (1) Preparation of catalyst
[0226] The all-silicon Beta molecular sieve was replaced with CeO2 molecular sieve, and the other conditions were the same as in Example 3 to prepare a 6% Ag-4% Mn / CeO2 catalyst.
[0227] (2) Catalyst performance verification
[0228] In order to verify the catalytic activity of 6% Ag-4% Mn / CeO2 molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0229] The CeO2 catalyst prepared in this comparative example has an ozone elimination rate of more than 68% in 6 hours and more than 65% in 12 hours under the test conditions. The ozone elimination curve changes with time as shown in FIG. Figure 6 shown.
[0230] Comparative Example 7
[0231] (1) Preparation of catalyst
[0232] Referring to the preparation method in Example 3, the all-silicon Beta molecular sieve was replaced with an aluminum-rich Beta molecular sieve (Si / Al=4). The other conditions were exactly the same as in Example 3 to prepare a 6% Ag-4% Mn / aluminum-rich Beta molecular sieve catalyst.
[0233] The nitrogen adsorption results of this example are as follows Fig.12 As shown in the figure, there is no hysteresis loop in the nitrogen adsorption diagram, indicating that the catalyst does not have mesopores. Fig.14 As shown, it indicates that its hydrophobicity is poor, which is also one of the reasons for the poor catalyst activity.
[0234] (2) Catalyst performance verification
[0235] In order to verify the catalytic activity of the aluminum-rich Beta molecular sieve catalyst, it was heated at a humidity of RH = 65% and a space velocity of 840000 h -1 , the ozone elimination test was carried out under the condition of reaction temperature of 30℃.
[0236] In this example, a 6% Ag-4% Mn / aluminum-rich Beta molecular sieve catalyst was prepared. Under the test conditions, the ozone elimination rate was above 61% in 6 hours, above 57% in 12 hours, and above 45% in 60 hours. The ozone elimination curve changes with time as shown in FIG. Figure 8 shown.
[0237] From the above experimental data, we can see that:
[0238] The all-silicon Beta catalyst provided by the present invention is heated to 30°C, RH=65-85% and 840000h. -1 It can maintain high-efficiency and long-term ozone elimination activity under space velocity conditions (reaction time 6 to 120 hours). Among them, the 6% Ag-4% Mn / all-silicon Beta molecular sieve catalyst can still maintain an ozone elimination efficiency of more than 85% under extreme conditions of 120 hours of reaction. One of the important influencing factors is that compared with the Mn2O3 and activated carbon carriers used in the prior art, the all-silicon Beta molecular sieve used in the present invention has mesopores and stronger hydrophobicity; since AgMnO2 with better ozone catalytic decomposition activity is generated during the reaction process, it is more beneficial to the ozone elimination reaction.
[0239] Therefore, compared with the ozone elimination catalyst using activated carbon and Mn2O3 as carriers in the prior art, the catalyst of the present invention has significant advantages in terms of moisture resistance, high space velocity and catalysis at low temperature.
[0240] The applicant declares that the above is only a specific implementation mode of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily thought of by those skilled in the art within the technical scope disclosed by the present invention are within the protection scope and disclosure scope of the present invention.
Claims
1. An all-silicon Beta molecular sieve catalyst for ozone elimination, characterized in that: The catalyst is obtained by using an all-silicon Beta molecular sieve with a three-dimensional twelve-membered ring BEA structure as a carrier, and loading Ag and Mn elements in a precursor solution on the molecular sieve in sequence through a two-step impregnation method; wherein the mass percentage of the Ag element in the catalyst is 1.0-10.0%, and the mass percentage of the Mn element in the catalyst is 1.0-10.0%.
2. The method for preparing the all-silicon Beta molecular sieve catalyst according to claim 1, characterized in that: The Ag and Mn elements in the precursor solution are loaded on the BEA structure molecular sieve in sequence through a two-step impregnation method; specifically including: (1) adding powdered all-silicon Beta molecular sieve to a precursor solution containing an Ag element, mixing them evenly and performing an impregnation treatment; subjecting the impregnated mixture to ultrasonication, stirring and rotary evaporation to obtain a solid, and then subjecting it to drying and calcining to obtain a powdered catalyst precursor; (2) adding the catalyst precursor to the precursor solution containing the Mn element, mixing them evenly and performing an impregnation treatment; the impregnated mixture is subjected to ultrasonication, stirring and rotary evaporation to obtain a solid, and then subjected to drying and calcination to obtain a powdered all-silicon Beta molecular sieve catalyst; By changing the dosage relationship between the two precursor solutions and the all-silicon Beta molecular sieve, the mass proportion of Ag and Mn elements in the all-silicon Beta molecular sieve catalyst is adjusted.
3. The preparation method according to claim 2, characterized in that: The all-silicon Beta molecular sieve has a three-dimensional twelve-membered ring BEA structure, with mesopores on its surface and a specific surface area of 500 to 700 m 2 .g -1 .
4. The preparation method according to claim 2, characterized in that: The precursor solution containing the Ag element refers to a silver nitrate solution, and the precursor solution containing the Mn element refers to a manganese nitrate solution. The concentrations of the two precursor solutions are both 0.1 mol / L.
5. The preparation method according to claim 2, characterized in that: The immersion treatment is carried out at room temperature for 10 to 12 hours.
6. The preparation method according to claim 2, characterized in that: The ultrasonic treatment was carried out at room temperature for 1 h at a frequency of 45 Hz.
7. The preparation method according to claim 2, characterized in that: The temperature during the rotary evaporation treatment is 80° C. and the rotation speed is 70 rpm.
8. The preparation method according to claim 2, characterized in that: The temperature during the drying process is 80° C. and the time is 2 hours.
9. The preparation method according to claim 2, characterized in that: The heating rate during the calcination process is 5°C / min, the calcination temperature is 450-550°C, and the calcination time is 4-6h; after the calcination is completed, the calcination is naturally cooled to room temperature.
10. A method for catalytically eliminating ozone using the all-silicon Beta molecular sieve catalyst according to claim 1, characterized in that: include: The catalyst is loaded in a fixed bed reaction device, and then the reaction gas containing ozone and saturated water vapor is passed through the catalyst bed in a continuous flow manner, and the ozone is decomposed into oxygen through a catalytic reaction; during the catalytic reaction process, the reaction temperature is controlled to be 30°C, and the volume hourly space velocity of the reaction gas is 840,000 h -1 The relative humidity during the reaction is 65-85%, and the reaction time is 6-120h.
Citation Information
Patent Citations
Ozone-eliminating catalyst using active carbon as carrier
CN102101052A
Manganese oxide catalyst for catalyzing ozonolysis and preparation method thereof
CN109603817A
Silver-manganese catalyst for decomposing ozone as well as preparation method and application of the silver-manganese catalyst
CN110711579A
Supported silver-manganese catalyst as well as preparation method and application thereof
CN112473665A
Full-silicon ZSM-5 molecular sieve catalyst for room-temperature formaldehyde purification and preparation method
CN108246351A